Peter Lilienthal : a cinema of exile and resistance - Sandberg, Claudia (Film Europa, 2021)
"Best known for his 1979 film David, Peter Lilienthal was an unusual figure within postwar filmmaking circles. A child refugee from Nazi Germany who grew up in Uruguay, he was uniquely situated at the crossroads of German, Jewish, and Latin American cultures: while his work emerged from West German auteur filmmaking, his films bore the unmistakable imprints of Jewish thought and the militant character of New Latin American cinema. Peter Lilienthal is the first comprehensive study of Lilienthal's life and career, highlighting the distinctively cross-cultural and transnational dimensions of his oeuvre, and exploring his role as an early exemplar of a more vibrant, inclusive European film culture"--